Comparative Study Of Honey Collected From Different Flora Of Algeria - Rebiai, A.; Lanez, T. (University of Eloued جامعة الوادي, 2014)
The aim of the present study was to evaluate the physical and chemical properties of five Algerian unifloral types of honey. Several physical parameters of honey, such as pH, moisture content, electrical conductivity, total dissolved solids, color intensity and total sugar content, were measured. The mean pH, moisture content, EC and water insoluble solids of Algerian honey were 4.41± 0.58, 15.3 ± 1.5%, 0.324± 0.116 mS/cm and 0.141± 0.065%, respectively. The mean color was 81 ± 72 mm Pfund. The majority of honey samples test results (moisture content, electric conductivity and acidity) levels were within the acceptable range of world honey standards.
Articale in Journal of fundamental and Applied Sciences Vol. 06 N. 01
Keywords: Apis mellifera, biochemical characters, unifloral honey, physical characteristics